Russian Cosmism in the Design of the Urban Environment of the Soviet Union in the 50-60s of the Twentieth Century - A. V. Astakhova (Дискурс)
Introduction.  The  purpose   of  the  article  is  to  illustrate  the  steady  influence   of  the philosophy of Russian cosmism  on the formation  of the urban environment  of the Soviet Union in the 50-60s  of the 20th  century. The authors  set the task to reveal that the motives of  conquering   nature,  associated  with the  achievement  of  the  ideals  of  communism, correspond to the ideals of Russian cosmism.  Cosmism is observed  everywhere  in Soviet art, but in the text the emphasis  is placed on architecture as one  of the main formations forming the city system  at the peak of urbanization  and influencing the consciousness of the Soviet person.Methodology and sources. A comparative analysis of the philosophical concepts of Russian cosmism  and Soviet ideas  of expansive  conquest of space  is carried  out. Periodicals  and works  of  art  from  the  Soviet  Union  are  analyzed.  The  article  also  outlines  the  main philosophical  paradigms  of  philosophers   based   on  the  works  of  the  founders   of  the philosophy of cosmism (N.F. Fedorov, K.E. Tsiolkovsky,  V.I. Vernadsky).Results and discussion. It is revealed that the motives of the conquest of nature, associated with the  achievement of the  ideals  of communism,  correspond to  the  ideals  of Russian cosmism. The practical and organic nature of Soviet architecture is evident. It was expressed in  block  construction   in  order  to  solve  the  housing  issue,  but  also  in  more  complex structures  designed  to  confirm  the  power  of the  Soviet people.  It is illustrated  that  the cosmic  forms  in Soviet architecture were defined  literally in two formats:  the  first as the personification  of rockets  in the  form  of TV towers,  the  second  as  the  personification  of plates in the embodiment of the architecture of circuses.Conclusion. The author concludes that the images of celestial architecture, intended for the speedy  exploration  of  the  cosmic  expanses, were  literally perceived  by young romantic architects  who found the ideal justification for their projects.